2011
DOI: 10.1111/j.1747-0285.2011.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Amyloid Structure Using Chemical Probes

Abstract: Alzheimer's disease (AD) is a common neurodegenerative disorder characterized by the deposition of amyloids in the brain. One prominent form of amyloid is composed of repeating units of the amyloid-b (Ab) peptide. Over the past decade, it has become clear that these Ab amyloids are not homogeneous; rather, they are composed of a series of structures varying in their overall size and shape and the number of Ab peptides they contain. Recent theories suggest that these different amyloid conformations may play dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 125 publications
2
148
1
Order By: Relevance
“…Infrared spectroscopy and x-ray diffraction have demonstrated the presence of significant amounts of ␤-sheet structure in A␤42 protofibrils and fibrillar oligomers (60 -62) that appear as the earliest fibrillar aggregates within the A␤ amyloidogenic pathway (47) and are putatively a major cytotoxic A␤ species (63). It was already demonstrated that ThT recognizes prefibrillar A␤ aggregates (64) and that the ThT fluorescence was only modestly increased (1.5-fold) when compared with fibrils (Ͼ100-fold). The lower ThT fluorescence of prefibrillar or oligomeric A␤ aggregates can be explained by the lower ␤-sheet content of oligomers (ϳ48 -57%) when compared with fibrils (61).…”
Section: Discussionmentioning
confidence: 99%
“…Infrared spectroscopy and x-ray diffraction have demonstrated the presence of significant amounts of ␤-sheet structure in A␤42 protofibrils and fibrillar oligomers (60 -62) that appear as the earliest fibrillar aggregates within the A␤ amyloidogenic pathway (47) and are putatively a major cytotoxic A␤ species (63). It was already demonstrated that ThT recognizes prefibrillar A␤ aggregates (64) and that the ThT fluorescence was only modestly increased (1.5-fold) when compared with fibrils (Ͼ100-fold). The lower ThT fluorescence of prefibrillar or oligomeric A␤ aggregates can be explained by the lower ␤-sheet content of oligomers (ϳ48 -57%) when compared with fibrils (61).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ dimers and their EGCG complexes were resolved in the 5 + state at m/z 1,733, 1,824, and 1,916, respectively. The relative abundance of Aβ dimers was significantly increased in samples incubated with EGCG compared with Aβ samples without any additional molecules or with ThT (a fluorescent probe that binds to Aβ fibrils, but not monomers or small oligomers) (40) (Fig. 2D).…”
Section: Egcg Directly Binds To Aβ Peptide and Causes Conformational mentioning
confidence: 99%
“…Some residues in Ab peptides are crucial for Ab aggregation, fibrilization, and conformational change. 35,36 Because of its Ab-binding function, DBP has a physiological significance in the pathogenesis of AD, but the contribution of the DBP-Ab interaction required elucidation. We first determined that DBP can bind to Ab and inhibit Ab oligomerization, and can influence Ab-mediated neuronal death in vitro.…”
Section: Discussionmentioning
confidence: 99%